PERAN CULTURAL INTELLIGENCE (CQ) DALAM KEPEMIMPINAN LINTAS BUDAYA (Studi Fenomenologi pada Gandhi Memorial Intercontinental School Semarang) - Subroto, Setyoningsih; Mas’ud, Fuad (Diponegoro Journal of Management, 2016)
There were several studies about expatriate leadership that conducted in Indonesia, but those are only focuses on the experience of living and working abroad. Consequently, this study aims to investigate the role of cultural intelligence (CQ) in cross-cultural leadership effectiveness, within the context of Indian-Indonesian cultural differences. Besides, what kind of leadership style that practiced by an expatriate leader as the result of CQ's role. This study used a qualitative method and conducted in one of the international schools in Semarang. The participants of this study contain 5 peoples (an Indian Principal, 2 school coordinators, and 2 teachers). Each participant delivered briefly about all the points that used in this study. The data were gathered by using in-depth interviews to revealed that all aspects in CQ (metacognitive, cognitive, motivational, behavioral) thoroughly have the main role in the Principal’s cross-cultural leadership effectiveness. The result of the data analysis indicate that the Principal has some characteristics of an effective leader, such as communicative, pay attention to the well-being of the staffs, listen carefully to the suggestion from the staffs, and directly see the conditions that faced by the staffs. Besides, the role of CQ also resulted in the Principal's leadership style, which shows bureaucratic but with a touch of nurturant side inside. The Principal is task-oriented, but still, keep a good relation with the staffs through motivation and praise.